Adolescents' sustainability concerns and reasons for not consuming sustainably. (16th November 2014) - Francis, Julie E.; Davis, Teresa
Abstract Many consumers report being concerned about sustainability but they do not necessarily consume in a sustainable manner. Understanding why this occurs is vital to encouraging sustainable consumption practices. Understanding the phenomenon in relation to adolescents is particularly important. In addition to being a significant segment of current consumers, adolescents are learning consumption habits and preferences that they will carry into adulthood. This research contributes to the domain by fulfilling two research objectives. The first objective was to develop and use a scale for measuring adolescents' sustainability concerns (ASC). The second objective was to identify and examine adolescents' reasons for not consuming sustainably. The research used a three‐stage multi‐method design that included small group interviews and two online surveys with adolescents aged 12 to 17 years. The ASC scale that we produced identifies 14 key sustainability concerns across the dimensions of environment, well‐being and society. The reasons for not consuming sustainably varied across these dimensions. For example, the most frequently reported reasons in the environmental dimension included cost and convenience whereas peer pressure and hedonic preferences were the dominant reasons for well‐being. More broadly, three groups of reasons for unsustainable consumption emerged. These included (i) limited application of sustainability concerns across consumption; (ii) deviating from concerns due to competing priorities; and (iii) limiting or eliminating personal responsibility. The contributions of this research have theoretical, methodological and practical implications for consumer researchers, social marketers and policy makers.